Strategi Membangun Karakter Anak Usia Sekolah Dasar (Telaah Kritis Buku “Alhamdulillah Anakku Nakal” Karya Miftahul Jinan dan Choirus Syafruddin) - Huzuwah Huzuwah; Ahmad Shofiyuddin Ichsan; Rohmat Dwi Yunianta (STAI Serdang Lubuk Pakam, 2021)
A naughty child is a test from God who has to be lived with the right solution. So, parents should be grateful if they haave a naughty child. This research aims to determine the strategy to build the child character of elementary school in the book